Pengembangan dan Penerapan Nilai – Nilai Karakter Dasar pada Peserta Didik di SDN NO. 101112 Sipange - Hasibuan, Sri yanti; Siregar, Rini Kesuma (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aimed to analyses the application of basic character values to grade 6 students at SDN No. 101112 Sipange. The character principles that are the focus of the study include honesty, responsibility, discipline, cooperation, and respect for others. This study applies a qualitative approach with data collection techniques through observation, interviews, and documentation. The findings of the study indicate that basic character values have been applied through various learning activities, although there are some challenges in the consistency and internalization of these values. Further efforts are needed to improve the effectiveness of the application of character values through collaboration between teachers